Correlation of Nutrition Education Model for Pregnant Women In Industrial Areas To Increase Knowledge of Nutrition, Nutritional Behavior, and Hemoglobin Levels of Pregnant Women - Lasiyati Yuswo Yani; Raras Merbawani; Asef Wildan Munfadlila (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Mojokerto is an industrial city which accounts for as much as 40% of the total female employees of reproductive age in the East Java region. The health status of pregnant women in industrial areas is something that must be considered in order to produce a superior Indonesian generation. The research design used the "Quasi-experimental pre post design" method. The sample of this study was 51 pregnant women in industrial areas. Treatment is in the form of nutrition education for pregnant women after the mother has confirmed knowledge of knowledge, nutritional behavior and Hb (hemoglobin) levels. The results showed that the knowledge of pregnant women increased 73% after increasing behavior, 78% increased behavior and increased mean Hb from 11.64 to 12.14. This study proves that the nutrition education model for pregnant women in industrial areas has a positive correlation with maternal nutritional knowledge, nutritional behavior and Hb levels of pregnant women